REKAYASA DAN UJI COBA ALAT KABEL LAYANG Expo-2000 GENERASI-3 DALAM PENGELUARAN KAYU PADA LERENG CURAM - Wesman Endom; Soenarno (Jurnal Penelitian Hasil Hutan, 2015)
The engineering and trial testing on the skyline system tool of third Generation Expo-2000 powered by 13-HP engine was conducted to look into its performance for exstracting wood logs from the forest at steep terrain. This undertaking took place at Forestry District Resort of Tanggeung, Forestry District of Cianjur, the State-Owned Forest Enterprise Unit III, Cibatu Village, West Java. Results revealed that working productivity was 1.72 m³ of wood/hour, with the entire cost of tool ownership and wood extraction at Rp 138,587.39/hour or being equal to Rp 80,346.45/m³.